2015
DOI: 10.1007/s00066-015-0902-7
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog pathway inhibitor in combination with radiation therapy for basal cell carcinomas of the head and neck

Abstract: The combination of vismodegib and radiation seems feasible and the initial results are promising. In our cohort, there was no increase in unexpected side effects. Further research is needed to evaluate the significance of this combined therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
1
12
0
7
Order By: Relevance
“…In phase II clinical trials, vismodegib treatment resulted in an increased median survival of one year in comparison with patients receiving a standard treatment [ 158 , 159 ]. These results suggested that vismodegib decreased the CSCs population through Hedgehog inhibition, being a promising strategy to the usage of vismodegib as a combinatory treatment with, for example, radiotherapy to target both non-CSC and CSC to remove all tumor cells [ 160 , 161 ].…”
Section: Treatments and Approachesmentioning
confidence: 99%
“…In phase II clinical trials, vismodegib treatment resulted in an increased median survival of one year in comparison with patients receiving a standard treatment [ 158 , 159 ]. These results suggested that vismodegib decreased the CSCs population through Hedgehog inhibition, being a promising strategy to the usage of vismodegib as a combinatory treatment with, for example, radiotherapy to target both non-CSC and CSC to remove all tumor cells [ 160 , 161 ].…”
Section: Treatments and Approachesmentioning
confidence: 99%
“…Hh inhibitors cyclopamine, LDE225 and GANT61 have been reported to sensitize cancer cells in vitro and in vivo to photon irradiation (115,165,(213)(214)(215). Several small clinical studies investigated the combination of photon irradiation with the Hh inhibitor vismodegib and reported that this combination has radiosensitizing effects in basal cell carcinomas (216)(217)(218). In addition, Hh signaling is an important pathway in CSC evolution and may have an impact on the intrinsic radioresistance of these cells.…”
Section: Inhibition Of Hedgehog Pathwaymentioning
confidence: 99%
“…If this radiosensitization also appears in cancer cells, the combination of Efavirenz with radiotherapy might improve tumor control. New combination strategies of radiosensitizing agents and radiotherapy may improve future treatment schemes ( 12 , 13 ). These results suggest that Efavirenz may be a promising new drug against cancer either alone or in combination with radiotherapy.…”
Section: Introductionmentioning
confidence: 99%